EFFORTS TO INCREASE PREGNANT WOMEN'S KNOWLEDGE ABOUT HIGH-RISK PREGNANCY WITH HEALTH EDUCATION - Handayani, Evika Putri; Jannah, Muliatul; Rahmawati, Alfiah (Transpublika Publisher, 2022)
Pregnancy is a physiological condition that can become pathological if there are complications that affect the health of both the mother and the baby. Pregnant women need to be aware of potential high-risk pregnancy factors and understand the importance of early detection. Health education is an essential tool for improving pregnant women's knowledge in this area. The aim of this study is to explore the impact of health education on pregnant women's knowledge about high-risk pregnancy. To achieve this, we conducted a review of existing research sources obtained from Google and Google Scholar. The sources were taken within the last five years, from 2018 to 2022. A total of 13 articles were identified, consisting of national and international journals that focused on pregnant women who received interventions in the form of health education about high-risk pregnancy. The findings suggest that health education has a positive impact on pregnant women's knowledge and can help reduce the risks associated with high-risk pregnancies.